Vinpocetine alleviate cerebral ischemia/reperfusion injury by down-regulating TLR4/MyD88/NF-κB signaling - Wu, Li-Rong (Oncotarget, 2017)
Inflammatory responses play crucial roles in cerebral ischemia/reperfusion injury. Toll-like receptor 4 (TLR4) is an important mediator of the neuroinflammatory response to cerebral ischemia/reperfusion injury. Vinpocetine is a derivative of the alkaloid vincamine and exerts an anti-inflammatory effect by inhibiting NF-κB activation. However, the effects of vinpocetine on pathways upstream of NF-κB signaling, such as TLR4, have not been fully elucidated. Here, we used mouse middle cerebral artery occlusion (MCAO) and cell-based oxygen-glucose deprivation (OGD) models to evaluate the therapeutic effects and mechanisms of vinpocetine treatment. The vinpocetine treatment significantly reduced mice cerebral infarct volumes and neurological scores. Moreover, the numbers of TUNEL+ and Fluoro-Jade B+ cells were significantly decreased in the ischemic brain tissues after vinpocetine treatment. In the OGD model, the vinpocetine treatment also increased the viability of cultured cortical neurons. Interestingly, vinpocetine exerted a neuroprotective effect on the mouse MCAO model and cell-based OGD model by inhibiting TLR4-mediated inflammatory responses and decreasing proinflammatory cytokine release through the MyD88-dependent signaling pathway, independent of TRIF signaling pathway. In conclusion, vinpocetine exerts anti-inflammatory effects to ameliorate cerebral ischemia/reperfusion injury in vitro and in vivo. Vinpocetine may inhibit inflammatory responses through the TLR4/MyD88/NF-κB signaling pathway, independent of TRIF-mediated inflammatory responses. Thus, vinpocetine may be an attractive therapeutic candidate for the treatment of ischemic cerebral injury or other inflammatory diseases.